Do Conservative Media Provide a Forum for Skeptical Voices? The Link Between Ideology and the Coverage of Climate Change in British, German, and Swiss Newspapers. Issue 4 (4th July 2017) - Schmid-Petri, Hannah
ABSTRACT: This study analyzes whether the ideological orientation of a newspaper has an influence on the salience of skeptical arguments (trend, attribution, impact, and response skeptics) in the coverage of climate change in the UK, Germany, and Switzerland, and examines whether certain newspaper titles act as advocates of the skeptical countermovement. A quantitative content analysis of a broad newspaper sample for each country over the course of one year (June 2012–May 2013) was conducted. The results reveal that conservative newspapers do not amplify skeptical voices in general; the difference between conservative and more liberal outlets is only found in the case of impact and response skepticism. Second, in each country, certain conservative newspapers are particularly open to skeptical arguments.